Uji In-Vivo Ekstrak Daun Sawo Manila (Manilkara zapota) Terhadap Pertumbuhan Escherichia coli - Anita, Anita; Fatmawati, Andi; Muawanah, Muawanah; Widyanti, Tuty; Jasman, Henra; Musa, Bilkis; Prastiwi Djamaluddin, Indra (Universitas PGRI Palembang, 2024)
Sawo manila (Manilkara zapota) is a member of the sapotaceae, which contains active chemical compounds such as saponins, tannins, and flavonoids that can inhibit and kill several bacteria, one of which is Escherichia coli. Escherichia coli is a normal flora bacteria in the digestive tract but will become pathogenic if its number in the digestive tract increases so that it can cause diarrhea. The aim of this research was to determine the effectiveness of Sawo manila (Manilkara zapota) leaf extract against Escherichia coli. Experimental laboratory work was done where Sawo manila leaves (Manilkara zapota) were powdered and then extracted using the maceration method. The inhibitory power test of Sawo manila leaf extract (Manilkara zapota) with concentrations of 50%, 75%, and 100% was carried out using the Kirby-Bauer diffusion method on Mueller Hinton Agar (MHA) media with an incubation period of 24 hours at 37°C. The test results showed that Sawo manila leaf extract (Manilkara zapota) at concentrations of 50%, 75%, and 100% did not contain an inhibitory zone. It was concluded that Sawo Manila (Manilkara zapota) was not effective against Escherichia coli.